War room : prayer is a powerful weapon - Fabry, Chris, 1961-; Kendrick, Alex, 1970-; Kendrick, Stephen, 1973- (Carol Stream, Illinois : Tyndale House Publishers, Inc., 2015)
When real-estate agent Elizabeth Jordan meets elderly widow Clara Williams, a visit to the elder woman's prayer room helps Elizabeth realize that her mounting problems at home are surmountable with the help of God.
"Based on the screenplay by Alex Kendrick and Stephen Kendrick."
Keywords: Dysfunctional families -- Fiction; Marriage -- Fiction; Domestic fiction; Christian fiction